Benefit of rectal washout for anterior resection and left sided resections. (January 2016) - Siddiqi, Najaf; Abbas, Muhammad; Iqbal, Zafar; Farooq, Muhammad; Conti, John; Parvaiz, Amjad
Abstract: Purpose: To assess the effectiveness of rectal wash out in preventing local recurrence for patients who undergo anterior resection for recto-sigmoid cancer. Materials and methods: A best evidence topic was constructed according to a structured protocol. Medline 1948–2015 and EMBASE 1980 to 2015 using the OVID interface: ( Rectal) AND (Washout) AND (Anterior Resection). In addition, the reference lists of the relevant papers were searched. Outcomes: Eight papers among the 17 relevant articles were identified as representing the best evidence including 3 prospective non-randomized studies, 1 retrospective non randomized study and 4 meta-analyses. Conclusions: On the basis of current evidence, rectal washout does not stop local recurrence of cancer after anterior resection or left sided colonic resection, but it may reduce the rate of local recurrence. A randomised controlled trial to address this issue would formally answer this question. Highlights: No randomized study has been undertaken on this subject and almost all the studies favoured a randomized control trial. Rectal washout does not stop local recurrence of cancer, but it may reduce the rate of local recurrence. A randomised controlled trial including surgical techniques utilised in recent years would formally answer the question.